The Effect Of The Think Pair Share Learning Model On Grade XI Students' Perception Of Democracy - Elizabeth Br. Tinambunan; Hotmaida Simanjuntak; Kondios Mei Darlin Pasaribu (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
The purpose of this study was to determine the perception of class XI students of SMA METHODIST 7 MEDAN before and after using the think pair share learning model, and to determine the effect of the Think Pair Share (TPS) learning model on class XI students' perceptions of the concept of democracy. In this study, the researcher used a quantitative research method, namely a research method that involves testing the relationship between variables measured by research instruments so that numerical data can be analyzed based on statistical procedures. Based on the research data and data analysis, it can be concluded that the think pair share learning model can increase the influence of students' perceptions of democracy and can be proven by the results of descriptive pre-test (before) and post-test (after) treatment obtained an average of 79.87 and 90.28. The results of the normality test The sig value in the pre-test is 0.231> sig value 0.05 (5%) meaning H0 is accepted and the sig value in the post-test is 0.006> sig value 0.05 (5%) meaning H0 is accepted, it can be concluded that the pre-test data is normally distributed and the post-test data is normally distributed. Based on the comparative hypothesis test of the pairad sample test output above, the sig value is 0.000> sig value 0.05 (5%) which means H1 is accepted and H0 is rejected. so that it can be concluded overall that there is an influence of student perception before and after the use of the think pair share learning models